1984
DOI: 10.1111/j.1751-0813.1984.tb06012.x
|View full text |Cite
|
Sign up to set email alerts
|

A congenital vascular naevus in a foal

Abstract: This paper describes a case of a congenital vascular malformation in the skin of a colt. The lesion arose at the coronary border of the right hind leg. The microscopic structure of a biopsy suggested that the lesion, consisting of multiple foci of closely-packed convoluted small vessels in the dermis, represented a marked exaggeration of glomi which normally occur in considerable numbers in this region of the skin. On the basis of the clinical, macroscopic and histological findings, this lesion was considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 3 publications
0
28
0
1
Order By: Relevance
“…It was suggested that in this mare, a teratoma had developed initially and that the carcinoma arose from epitheloid elements within the teratoma. Perhaps the same may hold for an ovarian cystadenoma associated with a dermoid-teratoma (27). Simultaneous and successive occurrence of granulosacell tumour was reported in two mares (38,43).…”
Section: Ovarian Teratomasmentioning
confidence: 80%
“…It was suggested that in this mare, a teratoma had developed initially and that the carcinoma arose from epitheloid elements within the teratoma. Perhaps the same may hold for an ovarian cystadenoma associated with a dermoid-teratoma (27). Simultaneous and successive occurrence of granulosacell tumour was reported in two mares (38,43).…”
Section: Ovarian Teratomasmentioning
confidence: 80%
“…Treatment options for cutaneous vascular malformations vary. As the lesions are fairly benign, conservative management can include simple monitoring of the lesion for change in character, excessive bleeding, and chronic infection 3,12 . However, if the lesion is causing significant blood loss, is interfering with normal function due to location, or is becoming repeatedly infected, removal is recommended 12,14,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, the terminology used to describe these lesions is confusing: hemangioma [1], vascular hamartoma [2,3], vascular nevus [4] and hemangioendothelioma [5], vascular nevus, lobular capillary hemangioma, and proliferative angioma [6]. These lesions are usually solitary, ranging 6 to 30 cm in diameter, and they usually are seen as dark, alopecic, hyperkeratotic plaques, or well-circumscribed, firm to fluctuant nodules with normal, alopecic, or ulcerated skin (verrucous hemangioma).…”
Section: Introductionmentioning
confidence: 99%